Entrepeneurship (ENT300) Sweet Sensation Cake / Yenny Hasmida Karim... [et al.] - Karim, Yenny Hasmida; Shahni, Zaimah; Christopher Grai, Desmond Unyu; Mardan, Abdul Samat
Our company name is Sweet Sensation Cakes. The business of our company has been decided on the form of partnerships. Each partner has contributes certain amount of capital as agreed in our agreement. Our business activity is to offers services by gives the customers an entertainment services which is drink, eat and make a discussion. All partners are encouraged and entitled to participate in all business management. We have agreed that Yenny Hasmida Binti Karim is the General Manager and Administrative Plan, Zaimah Binti Shahni as the Marketing Manager, Desmond Unyu Anak Christopher Grai as Operation Manager, also, and Abdul Samat Bin Mardan as the Financial Manager. The selection of each position based on consensus among all the partners and selected based on the criteria of experience, skill and ability. The management team will be led by the general manager and the other manager will help in other process. The task and responsibilities of a general manager is responsible involve in the process of controlling, leading, organizing as well as plan the entire business. The marketing manager will responsible in preparing the marketing process which includes the process of identifying the target market, determining the market size, identifying the competitors, determining the market share, developing the sales forecast and marketing strategies.